Cytotoxic Potential of Uncaria cordata (Lour) Merr. Ethyl Acetate Subfraction on T47D Breast Cancer Cells - Noveri Rahmawati; Enda Mora; Reyvia Rahma Ningsih Ningsih; Nurbaiti Nurbaiti (JSFK (Jurnal Sains Farmasi & Klinis), 2026)
Uncaria cordata is a plant that grows in Indonesia and is known locally as Akar kaik-kaik. The local communities have traditionally used it to treat cancer. A Preliminary study has shown that potential secondary metabolites in the plant extract exhibit cytotoxic activity. This study aims to determine the cytotoxic activity of subfractions obtained from ethyl acetate extracts of U. cordata leaves on T47D breast cancer cells. The dried leaves were extracted using ethyl acetate and then fractionated using vacuum liquid chromatography (VLC). The extracts and fractions were determined for their cytotoxic activity using the Brine Shrimp Lethality Test (BSLT) and MTT test. BSLT assay showed the results of the cytotoxic activity fraction (F3-F14) have an LC50 value of 24.0; 67.1; 98.8; 161.5; 102.6; 119.8; 18.3; 16.8; 43.1; 186.1; 54.3 and 29.9 µg/ml. The MTT assay revealed that the IC50 of the fractions F9, F10, and F14 were 15.81, 15.12, and 17.43 µg/mL, respectively. The three fractions exhibited a strong cytotoxic effect on T47D breast cancer cells. Therefore, it can be concluded that the three fractions, F9, F10, and F14, have a substantial cytotoxic effect on T47D breast cancer cells.